MANAJEMEN USAHA OLAHAN KELAPA “BATTE ANJORO” PADA KELOMPOK USAHA RUMAHAN LINGKUNGAN GALUNG BARAT KABUPATEN MAJENE - Muthmainnah, Arlistria; Erwin, Erwin; Anwar, Nursyam (Universitas Mataram, 2024)
Business management assistance to home-based business groups is one of the important efforts to increase the capacity and economic independence of the community. This activity aims to improve the management skills of the processed coconut business “Batte Anjoro” in home-based business groups in the West Galung Neighborhood, Majene Regency. The methods used in mentoring include improving the quality of processed coconut-based products, branding and packaging training, and digital-based marketing strategies. The results of the mentoring showed an increase in the knowledge and skills of group members in managing businesses, expanding marketing networks, and increasing sales turnover. In addition, the quality of processed coconut products has also improved, making them more competitive in local and regional markets. With this assistance, home-based business groups are expected to be able to operate more effectively and independently, and contribute to regional economic growth. Keywords: Business management, Processed coconut, Home-based business groups, Majene Regency.